High circulation of hepatitis B virus (HBV) precore mutants in Tunisia, North Africa. - Triki, H. (Cambridge University Press, 2000)
Hepatitis B Virus (HBV) e antigen (HBeAg), HBV DNA and precore mutations affecting HBeAg expression during active replication were studied in 72 Tunisian hepatitis B surface antigen (HBsAg) positive individuals: 30 asymptomatic carriers of the virus, 37 with chronic hepatitis and 5 with acute hepatitis. HBV DNA was detected in 44 patients, but only 20% of them expressed HBeAg. Precore mutant strains, with mutations at position 1896 or at positions 1896 and 1899, were detected by PCR-hybridization in 86 and 36% of patients, respectively. Wild-type strains were detected in 54% of patients. Precore mutants were found in chronically and in acutely infected individuals, in patients with severe and asymptomatic infections, in HBeAg positive as well as HBeAg negative individuals.These results show the high frequency of HBV precore mutants in Tunisia.